Chapter Monitoring Transformations of Urban and Natural Landscape in Mediterranean Cities by Promoting Landscape Setting Archetypes - Sopina, Ana; Bojanić Obad Šćitaroci, Bojana (Firenze University Press, 2025)
The research phenomenon of the ‘urban and natural landscape relation’ as landscape setting of cities, testifies to 25 centuries of urban culture in the Mediterranean. The holistic understanding of the landscape relation as a multidimensional phenomenon and changeability process presents a challenge in application to spatial planning. The research hypothesis introduces landscape archetypes as a conceptualisation principle that integrate various research fields and embody landscape reality, representation, and change. The applied research method of literature review sets spatial planning, collective psychology, and art photography as the main research fields for establishing landscape setting and landscape transformation archetypes. These landscape archetypes are verified by comparing the Mediterranean cases of Livorno, Ancona, and Dubrovnik. The landscape archetypes aid in dealing with the complex nature of landscape relations by acknowledging the values found in every landscape. Spatial planning, collective psychology, and art photography contribute to raising collective and individual landscape consciousness and foster a holistic approach to monitoring landscape transformations.